Dispersion of the third order optical nonlinearity & all-optical switching figures of merit in molecularly engineered polymers - Ryder, Kieran (Trinity College (Dublin, Ireland). School of Physics, 2002)
Solid state and solution measurements of the effective third order nonlinear absorption and refraction, have been earned out on poly (2,5-dioctyloxy-paraphenylene-vinylene-co-2,5- pyridinyl) (Pyridinyl PAV), poly (2,5-dioctyloxy-paraphenylene-vinylene-co-2,5-thienyl) (Thienyl-PAV), poly (2,5-dioctyloxy-paraphenylene-ethynylene-co-2,5-pyridinyl) (Pyridinyl-PAE) and poly (2,5-dioctyloxy-paraphenylene-ethynylene-co-2,5-thienyl) (Thienyl-PAE) using the Z-Scan experimental technique.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin